A Modular Method for the High‐Yield Synthesis of Site‐Specific Protein–Polymer Therapeutics. Issue 35 (21st July 2016) - Pang, Yan; Liu, Jinyao; Qi, Yizhi; Li, Xinghai; Chilkoti, Ashutosh
Abstract: A versatile method is described to engineer precisely defined protein/peptide–polymer therapeutics by a modular approach that consists of three steps: 1) fusion of a protein/peptide of interest with an elastin‐like polypeptide that enables facile purification and high yields; 2) installation of a clickable group at the C terminus of the recombinant protein/peptide with almost complete conversion by enzyme‐mediated ligation; and 3) attachment of a polymer by a click reaction with near‐quantitative conversion. We demonstrate that this modular approach is applicable to various protein/peptide drugs and used it to conjugate them to structurally diverse water‐soluble polymers that prolong the plasma circulation duration of these proteins. The protein/peptide–polymer conjugates exhibited significantly improved pharmacokinetics and therapeutic effects over the native protein/peptide upon administration to mice. The studies reported here provide a facile method for the synthesis of protein/peptide–polymer conjugates for therapeutic use and other applications. Abstract : The site‐specific and stoichiometric synthesis of protein/peptide–polymer therapeutics in high yield is enabled by a modular method that is based on a combination of recombinant expression, enzyme‐mediated ligation, and click chemistry. This approach is suitable for the conjugation of structurally diverse polymers to various protein and peptide drugs.